If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -7x + 57 Reorder the terms: y = 57 + -7x Solving y = 57 + -7x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 57 + -7x
| F(x)=74+3.7x | | 12x-24+8x+28=180 | | 61=5a-4 | | 2(x+4)(x+7)=(2x+1)(x-9) | | 2x^3-22x^2+60x=0 | | x(7x+5)-x=0 | | -4-11=7x+15-6x | | .03x+18000=90 | | 4(a-4)=2(a+5) | | -15=r-8 | | 7+2(x-3)-4x= | | y+1(9+24)-28=96 | | 5x+20=5x-18 | | 10+a=26 | | x(7x+5)-x(x)(x)=0 | | 5x^2+10x+8y^2-48y+37=0 | | 2(113-2c)+4c=226 | | 20+10x-(8x-12)=68 | | .03x+.07(18000-x)=90 | | 4k-(-6)=-2-(-16)-(-2) | | 6n-.7=11 | | 10+n=25 | | -18x^2+51x+8=0 | | X^2+6x+64=48 | | 9x^4-64=0 | | 4c^2+7x-15=0 | | 15+n=6 | | 3x^4-7x^2=0 | | (4x+2)-x=(2x-10) | | 9(2+v)+35v=14v | | .5x(x+4)=16 | | 69=12 |